2019
DOI: 10.3326/pse.43.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Citizens and the city: the case for participatory budgeting in the City of Zagreb

Abstract: sandra švaljek, ivana rašić bakarić, marijana sumpor: citizens and the city: the case for participatory budgeting in the city of zagreb public sector economics 43 (1) 21-48 (2019) 22 Abstract Since there is constant concern that local government heads allocate budget resources in favour of various pressure groups, the paper investigates whether local participatory budgeting can be implemented in order to better align budget allocation with citizens' needs in the Croatian context. The paper analyses the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We found out that the collaboration between the mayor and finance director is an important institutional factor affecting the adoption of the budget, with mutual trust, openness, and daily collaboration as the basis for good and timely performance of tasks and preparation and adoption of the local community's budget. Other research showed that local governments, representatives, and citizens often perceive public budgeting as a difficult administrative task that should be handled by experts who have specialized knowledge, technical skills, and experience [17]; we assumed that these experts are finance directors. In our research we made a step forward and claimed that the collaboration between the mayor and finance expert in preparing the budget is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…We found out that the collaboration between the mayor and finance director is an important institutional factor affecting the adoption of the budget, with mutual trust, openness, and daily collaboration as the basis for good and timely performance of tasks and preparation and adoption of the local community's budget. Other research showed that local governments, representatives, and citizens often perceive public budgeting as a difficult administrative task that should be handled by experts who have specialized knowledge, technical skills, and experience [17]; we assumed that these experts are finance directors. In our research we made a step forward and claimed that the collaboration between the mayor and finance expert in preparing the budget is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were several projects financed by international donors, aimed at fostering fiscal transparency and enabling citizens to involve themselves in budgetary decision-making. Citizen participation in the budget process is crucial for ensuring democratic, transparent and politically accountable decision-making in public finance (Švaljek, Rašić Bakarić and Sumpor, 2019). These authors find that public policy needs to focus on raising awareness among citizens of the ways they could influence the budget process.…”
Section: Citizens' Engagement: Perception About Economy and Politicsmentioning
confidence: 99%
“…For example, Pahl-Wostl and Hare (2004) reported on the importance of knowledge and information for long-term participatory management of integrated resource management projects. Several scholars also argued for increasing awareness and knowledge on environmental management and technical matters in promoting effective public participation (Kamaruddin et al, 2016; Švaljek et al, 2019; Zellatifanny et al, 2021). It is contended that self-efficacy and elements contributing to local empowerment could lead to a positive attitude towards participation.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%